The electrical characteristics of Nanosheet FET within the quasi-ballistic transport: Role of scattering and temperature variation - Shubham; Rajan Kumar Pandey (PLoS ONE, 2026)
The article highlights the effects of quasi-ballistic and diffusive transport on electron mobility, band gap, and electrostatic behavior in scaled Nanosheet FETs. It also provides comprehensive physical insight into the effects of different scattering mechanisms on the gate-length scaling process (from 16 nm to 6 nm) and their impact on performance metrics. The temperature is modeled from 220 K to 450 K to analyze its effect on electron mobility and the lateral electric field profile. It is observed that defects, such as oxygen vacancies, affect the work function of the gate stack region and induce scattering mechanisms at the oxide interface, thereby enhancing band-to-band and trap-assisted tunneling of electrons. Increased temperature in the device causes significant phonon scattering, resulting in approximately a 45% drop in the mobility, with a standard deviation of 328.7 cm²/V·s. The higher phonon and surface-scattering rates at elevated temperatures modify the band gap profiles, leading to a reduction of 48–72 meV in the band gap. Due to the reduced scattering and lower contact-poly pitch, the highest drive current is achieved at a 6 nm gate length in the quasi-ballistic and diffusive transport regimes. Gate-length scaling suffers from increased scattering rates and higher tunneling probabilities, leading to higher leakage current and a reduced I ON /I OFF ratio. Scattering mechanisms introduce resistance in the channel region, resulting in a drop in mobility. The electrostatic profiles and mobilities are mapped along the channel to comprehend the device operation at the scaled node.